Storytelling as a motivating tool for elementary students to use their school library an experimental study - Castillo, Moira L.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This was an experimental study that sought to prove the claim that the storytelling motivates the students belonging to use their school library. In the study, the independent variable is the storytelling that was conducted by the researcher, while the two dependent variables are the number of students who entered the school library and the number of books that they borrowed.
The researcher set a duration of ten (10) days for the pretest, five (5) weeks for the treatment and another ten (10) days for the posttest. The once-a-week 30-minute storytelling was conducted in Filipino. The statistical analysis of test of proportions was utilized to test the hypothesis. It was used to determine whether the proportion of the experimental group is significantly different from the control group during the pretest and the posttest. It was able to prove the alternative hypothesis that the storytelling motivates the students belonging to the experimental group to use their school library.
Based on the findings of the study, the researcher highly recommended that school libraries here in the Philippines include the storytelling as an extension work to further the aims of the library in attracting children to use the library and in promoting the love of reading.
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman.
Vita
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: School libraries -- Use studies. -- Philippines -- Quezon City; Story telling; University of the Philippines Integrated School